Aggressive behaviors in Small Schoolchildren: Array - Nicolae, Marius; Neaga, Susanu (New Trends in Psychology, 2020)
Abstract: Regarding the small schoolchildren it can be said that these reactions, the aggressive behaviors, are the result of the experiences of feelings of anger and frustration, that appear against the background of abilities of expression of the emotions and of emotional regulation insufficiently developed. Only in time, through different life experiences, children learn to gain better control over their own emotional reactions. Research indicates that these skills are essential for success at school, with family, with friends and on a professional level. When children are not aware of their own experiences, they may find it difficult to control their actions driven by the first impulse and to make appropriate decisions. In school, there are more and more conflicting situations between children of young school age, such as quarrels, misunderstandings or disputes, taking place in play contexts or daily interactions with colleagues at school. Due attention should be paid to constant and constantly supervised violent manifestations of children, both during class hours and during breaks. They need to be taught that when they are involved or witnessing violence, they should contact the teacher.